Double diffraction dissociation at the Fermilab Tevatron Collider - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Asakawa, T; Ashmanskas, W; et al. (2001)
Double diffraction differential cross sections in pp collisions at √s = 1800 and 630 GeV were measured. Results were compared with data at √s = 200 and 900 GeV and with predictions based on Regge theory and factorization. A factorization breakdown comparable in magnitude to that observed in single diffraction dissociation was found. The data are in agreement with the renormalized gap probability model.